Penguatan Sikap Kejujuran dan Tolong-Menolong Melalui Drama Enam Penyihir Penyelamatan Hutan di TK Bakti 2 Ngesrep Boyolali - Azizah, Annafi’ Nurul ‘Ilmi; Alifvia, Pinkan Tradya; Ananda, Afifah Fadhilah Surya; Rofi’ah, Anisatur; Salabila, Fatwa Naila; Nisa, Destria Choirun; Fajriati, Nurvita (CV. Devi Tara Innovations, 2025)
This community service initiative addresses the critical need for robust character education in early childhood, specifically fostering honesty and helping attitudes through an innovative drama performance titled